Struggle Of Anna Fitzgerald's Life In Jodi Picoult'sMy Sister',S Keeper Noyel (2004): An Indtwdual Psychological Approach - Mahastuti, Desty Rianata; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The problem of this study is to reveal how the struggle of life in major character. The objective of this study is to analyze the movie based on the structural elements and to analyze the major character in My Sister's Keeper novel based on an Individual Psychological Approach. This study is a literature. The type of this research is qualitative research. The object of this study is Jodi Picoult's My Sister's Keeper novel. The data source is primary and secondary data source. The primary data source taken from My Sister's Keeper novel itself, by Jodi Picoult and the secondary data source are about the biography novelist, some book, encyclopedias, website searching about My Sister's Keeper novel and another data related to this study. The method used for collecting data is Library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the researcher concludes that the problem faced by the major character is struggle to get her right in medical emancipation. In order to, the researcher used an Individual Psychological Approach such as Fictional Finalism, Inferiority Feeling, and Striving for Superiority, Social Interest, Style of Life, and Creative Power. By using this method, it is know how Anna Fitzgerald as major character can solve her problem that getting her medical emancipation from her parents.